Fuel Consumption and Collision Avoidance Strategy in Multi-static Orbit Formations - Jochim, E. F.; Fiedler, H.; Krieger, Gerhard (Acta Astronautica, 2011)
This paper analyses the fuel consumption of interferometric radar missions employing small satellite formations like, e.g., Cross-track Pendulum, Cartwheel, CarPe, or Trinodal Pendulum. Individual analytic expressions are provided for each of the following contributions: separation from a simultaneously injected master satellite, formation set-up, orbit maintenance, formation maintenance, and distance maintenance. For this, a general system of equations is derived describing the relative motion of the small satellites in a co-rotating reference frame. The transformation into Keplerian elements is carried out. To evaluate fuel consumption, three master satellites are assumed in different orbital heights, which are typical for Earth observation missions. The size of the exemplarily analysed formations is defined by remote sensing aspects and their respective fuel requirements are estimated. Furthermore, a collision avoidance concept is introduced, which includes a formation separation and formation set-up after a desired time period. © 2010 Elsevier Ltd.
DLR Import::2019-04-02
Keywords: Cartwheel; Multi-static orbit formations; Pendulum satellite formations; Relative satellite motion; SAR interferometry; Satellite manoeuvre costs